2008
DOI: 10.1037/a0012616
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of exposure therapy and cognitive restructuring for posttraumatic stress disorder.

Abstract: Previous studies have reported that adding cognitive restructuring (CR) to exposure therapy does not enhance treatment gains in posttraumatic stress disorder (PTSD). This study investigated the extent to which CR would augment treatment response when provided with exposure therapy. The authors randomly allocated 118 civilian trauma survivors with PTSD to receive 8 individually administered sessions of either (a) imaginal exposure (IE), (b) in vivo exposure (IVE), (c) IE combined with IVE (IE/IVE), or (d) IE/IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 47 publications
1
117
0
3
Order By: Relevance
“…For example, PE was found to be efficacious in treating PTSD related to physical and sexual assault (e.g., Foa et al, 1999;Foa, Hembree, et al, 2005;Resick, Nishith, Weaver, Astin, & Feuer, 2002;Resick, Williams, Suvak, Monson, & Gradus, 2012), military combat (Nacasch et al, 2011;Schnurr et al, 2007;Thorp, Stein, Jeste, Patterson, & Wetherell, 2012), motor vehicle accidents (Blanchard et al, 2003), and mixed traumas (Bryant et al, 2008;Marks, Lovell, Noshirvani, Livanou, & Thrasher, 1998). Importantly, the evidence for the efficacy of PE emerged from research centers around the world.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PE was found to be efficacious in treating PTSD related to physical and sexual assault (e.g., Foa et al, 1999;Foa, Hembree, et al, 2005;Resick, Nishith, Weaver, Astin, & Feuer, 2002;Resick, Williams, Suvak, Monson, & Gradus, 2012), military combat (Nacasch et al, 2011;Schnurr et al, 2007;Thorp, Stein, Jeste, Patterson, & Wetherell, 2012), motor vehicle accidents (Blanchard et al, 2003), and mixed traumas (Bryant et al, 2008;Marks, Lovell, Noshirvani, Livanou, & Thrasher, 1998). Importantly, the evidence for the efficacy of PE emerged from research centers around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some authors argue that if the mechanism of change (i.e., change in cognitions) is directly targeted (i.e., through cognitive interventions), treatment effects will be larger (Clark, 1999;Rachman, 1997). Several empirical studies confirm that the use of cognitive interventions (slightly) enhances treatment outcome (Bryant et al, 2008;Clark et al, 2006;Mattick, Peters, & Clarke, 1989;McMillan & Lee, 2010;Salkovskis, Hackman, Wells, Gelder, & Clark, 2007). Other studies, by contrast, have not found enhanced treatment effects when cognitive interventions were added to a behavioral treatment (Feske & Chambless, 1995;Koch, Spates, & Himble, 2004;Whittal, Thordarson, & McLean, 2005).…”
Section: Pathways To Change In One-session Exposure With and Without mentioning
confidence: 99%
“…Differences between studies can then be explained through differences in within-study control of therapy time (Bryant et al, 2008) or in the way in which exposure is combined with cognitive interventions (administered together or separately). Also, there might be differences in the extent to which different anxiety disorders are suitable for exposure (e.g., exposure to spiders might get more to the core of spider phobia than exposure to physical sensations does in panic disorder) or cognitive interventions (e.g., a Socratic dialogue might be more effective in the context of PTSD than in the context of specific phobia).…”
Section: Pathways To Change In One-session Exposure With and Without mentioning
confidence: 99%
“…O uso da reestruturação cognitiva é considerado uma opção eficaz em casos de fobia social (D'el Rey e Pacini, 2006), homens perpetuadores de violência doméstica (Norman e Ryan, 2008), raiva (Deffenbacher et al, 2000;Whiteman et al, 1987), TEPT (Bryant et al, 2008;Peres et al, 2007), dependência de tabaco (Shobola, 2007), compras compulsivas (Filomensky e Tavares, 2009) e regulação da emoção como em fobias e transtorno de ansiedade (Porto et al, 2008).…”
Section: Processo De Reestruturação Cognitivaunclassified